Highly toughening of PLLA-Based micropart via stretching induced stereocomplex crystal microstructure evolution - Yeping Xie; Jiayu Tan; Shijian Fang; Zhuo Zheng; Lei Yao; Yang Xu; Jian Li; Yinghong Chen; Ning Chen; Li Li (Materials & Design)
Polylactic acid (PLA) holds great potentials in biomedical applications, but its inherent brittleness restricts its versatility to a considerable degree. This study proposed a novel and heterogeneous modifier-free approach to enhance PLA’s toughness by leveraging the stretching induced evolution of stereocomplex crystal (SC) microstructures in situ formed during microinjection molding. By incorporating 10 wt% poly(D-lactic acid) (PDLA) into poly(L-lactic acid) (PLLA) through combining melt compounding and microinjection molding featuring extremely intense shear, we achieved a remarkable 10-fold increase in elongation at break (from 8.7 % to 87.2 %) while maintaining tensile strength (∼67 MPa). The structural analyses revealed a transition from phase-separated sea-island morphologies to deformable stereocomplex crystal PLA phase domains, which could serve as the physical crosslinking points facilitating stress transfer, and can be transformed into microfibril and shish-kebab structures upon drawing. Such the phase structure evolution could efficiently distribute stress and hence enhance toughness without sacrificing biodegradability or biocompatibility. This work develops a streamlined approach in simplifying conventional stereocomplex reinforcement strategies and thus offers a scalable method for developing fully biodegradable, and high-performance PLA-based materials suitable for diverse biomedical applications, such as bone tissue reconstruction.